The Art of Losing Yourself - Ganshert, Katie (Thorndike, Maine : Center Point Large Print, 2015)
"A contemporary novel of two sisters trying to find new life--one in her marriage and faith, the other desperate for a chance at a future"--
Keywords: Large type books; Love stories; Christian fiction